Metallocavitins as Promising Industrial Catalysts: Recent Advances - Shteinman, Albert A. (Frontiers in Chemistry, 2022)
The energy, material, and environmental problems of society require clean materials and impose an urgent need to develop effective chemical processes for obtaining and converting energy to ensure further sustainable development. To solve these challenges, it is necessary, first of all, to learn solar energy harvesting through the development of artificial photosynthesis. In our planet, water, carbon dioxide, and methane are such affordable and inexhaustible clean materials. Electro/photocatalytic water splitting, and also CO2 and CH4 transforming into valuable products, requires the search for relevant efficient and selective processes and catalysts. Of great interest is the emerging new generation of bioinspired catalysts—metallocavitins (MCs). MCs are attracting increasing attention of researchers as advanced models of metalloenzymes, whose efficiency and selectivity are well known. The primary field of MC application is fine organic synthesis and enantioselective catalysis. On the other hand, MCs demonstrate high activity for energy challenging reactions involving small gas molecules and high selectivity for converting them into valuable products. This mini-review will highlight some recent advances in the synthesis of organic substances using MCs, but its main focus will be on the rapid development of advanced catalysts for the activation of small molecules, such as H2O, CO2, and CH4, and the prospects for creating related technological processes in the future.